ANALISIS POTENSI ENERGI ANGIN MEMANFAATKAN KENDARAAN YANG BERGERAK DI JALAN PB SUDIRMAN PATRANG, JEMBER - Ramadhan Al Firdaus; Nasrul Ilminafik; Aris Muttaqin (Mechanical Engineering Department, Faculty of Engineering, Universitas Lambung Mangkurat, 2022)
The potential of wind energy on the highway by utilizing moving vehicles can produce wind speeds of up to 6 m/s depending on the speed, intensity, and size of the vehicle. The study was conducted to determine the potential for wind energy generated on Jalan PB Sudirman based on wind speed m/s on November 24-30 and December 11-17. The average wind speed on November 24 - 30, the highest is 3.1 m/s and the lowest is 1.9 m/s with characteristic wind gusts at 06-17 hours. The average wind speed on December 11-17 is the highest at 3, 8 and the lowest is 2 m/s with low wind characteristics, and gusts from 06 to 17. Based on the characteristics of the gusts of wind, two types of turbines that can rotate at low speeds were selected: HAWT TSD-500 cut-in 3 m/s and VAWT EN-5KW-H cut-in 2.5 m/s, The average power potential from November to December of the TSD-500 is 232.9 Watts and 443.7 Watts. The EN-5KW-H average power potential is 456.9 watts and 844.6 watts. EN-5KW-H can take advantage of wind speed with wind characteristics better than TSD-500.